WEBSITE SISTEM INFORMASI PEMETAAN PARIWISATA KABUPATEN LEBAK, PROVINSI BANTEN - Erica Yewinda; Ery Dewayani; Bagus Mulyawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2018)
Lebak Regency has a variety of natural attractions are exotic, interesting, and need to be visited but in the delivery of information is still only in the form of books, giving brochures and website which explains natural tourism in short description only and map feature through google maps.The purpose of this website is made as an alternative to the promotion of tourist areas of Lebak Regency. In addition, it is expected to facilitate the public and the tourists in getting information about nature tourism in Lebak Regency. The method used in data collection is the method of observation and interview method. Software development method used is System Development Life Cycle (SDLC) and programming language used is PHP and to manage database using PhpMyAdmin.The result of making this website is to use this website easily and natural tourism information presented are complete.